Antibodies to leukotoxin A from the periodontal pathogen Aggregatibacter actinomycetemcomitans in patients at an increased risk of rheumatoid arthritis - Martinsson, Klara; Di Matteo, Andrea; Öhman, Carina; Johansson, Anders; Svärd, Anna; Mankia, Kulveer; Emery, Paul; Kastbom, Alf (Frontiers in Medicine, 2023)
Objectives: Periodontitis and underlying bacteria have been linked to the development of rheumatoid arthritis (RA). One suggested pathogen is Aggregatibacter actinomycetemcomitans (A.a.), which express leukotoxin A (LtxA) that can citrullinate human proteins, providing a possible trigger for production of anti-citrullinated protein antibodies (ACPA). In the present paper we sought to determine the presence of antibodies towards LtxA in patients at risk of developing RA.Methods: Two prospective observational patient cohorts (one Swedish, one British) with symptomatic at-risk patients were studied. Anti-LtxA antibodies were analysed by a cellbased neutralisation assay in baseline serum and compared to 100 Swedish blood donors that served as controls.Results: Serum anti-LtxA levels or positivity did not differ between patients and blood donors. In the British cohort, anti-LtxA was more prevalent among ACPA positive arthralgia patients compared with ACPA negative arthralgia cases (24% vs 13%, p=<0.0001). In the Swedish at-risk cohort, anti-LtxA positive patients were at increased risk of progression to arthritis (Hazard ratio (HR) 2.10, 95% CI 1.04 -4.20), but this was not confirmed in the UK at-risk cohort (HR 0.99, CI 0.60-1.65).Serum anti-LtxA is not elevated before RA diagnosis, and associations with disease progression and ACPA levels differ between populations. Other features of the oral microbiome should be explored in upcoming periodontitis-related RA research.